2015
DOI: 10.1111/ijpo.12036
|View full text |Cite
|
Sign up to set email alerts
|

Childcare use and overweight in Finland: cross‐sectional and retrospective associations among 3‐ and 5‐year‐old children

Abstract: Beginning childcare before age 1, which is quite rare in Finland, and having attended several childcare places were associated with overweight even when adjusting for family socioeconomic status and other family background variables. The significance of these findings needs to be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Childcare attendance has been associated with obesity in children in Canada, China, Denmark, Finland, the United Kingdom (UK) and the United States (US) . The association may depend on the age of children in care – prior studies of infants have linked early care with obesity .…”
Section: Introductionmentioning
confidence: 99%
“…Childcare attendance has been associated with obesity in children in Canada, China, Denmark, Finland, the United Kingdom (UK) and the United States (US) . The association may depend on the age of children in care – prior studies of infants have linked early care with obesity .…”
Section: Introductionmentioning
confidence: 99%
“…Benjamin et al (2009) showed that infants who attended home-based child care early in life had an increased weight for length at 1 year and BMI at 3 years, suggesting that more research is needed into the food and physical activity policies of family child care homes. Additional studies in Denmark (Neelon et al 2015) and Finland (Lehto et al 2015) have demonstrated an association between starting child care before age 1 and an increased risk for later obesity. In 2011, the White House Task Force on Childhood Obesity supported the development of new national standards for healthy eating, encouraging breastfeeding, promoting physical activity, and limiting screen time in early-care settings (American Academy of Pediatrics, American Public Health Association, and National Resource Center for Health and Safety in Child Care and Early Education 2012).…”
Section: Child Care and Schoolmentioning
confidence: 98%
“…Broadly, those authors suggest CBC may protect against overweight by promoting a healthier diet and providing health care [62]. Yet other studies have found no association between CBC and childhood overweight [67][68][69][70][71][72][73][74]. Attending CBC could be associated with lower risk of child overweight or obesity through several pathways, including planned nutritional programs and learning environments, healthy eating, regular opportunities for physical activity, regular bedtime and rise time, and reduced screen time (eg, computers, mobile phones, television) [62,63,75,76].…”
Section: Viewpoints Papersmentioning
confidence: 99%